2018
DOI: 10.3389/fgene.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Signaling, Translational Control, and the Circadian Clock

Abstract: Almost all cellular processes are regulated by the approximately 24 h rhythms that are endogenously driven by the circadian clock. mRNA translation, as the most energy consuming step in gene expression, is temporally controlled by circadian rhythms. Recent research has uncovered key mechanisms of translational control that are orchestrated by circadian rhythmicity and in turn feed back to the clock machinery to maintain robustness and accuracy of circadian timekeeping. Here I review recent progress in our unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 92 publications
0
43
0
Order By: Relevance
“…Furthermore, based on our data, there is a need to determine the mechanistic link between diurnal changes and autophagy in the neural retina. There is considerable evidence that diurnal/circadian rhythm is associated with the induction of autophagy [44,53], a key regulator of autophagy; the mechanistic target of rapamycin (mTOR) is regulated by the circadian clock [54] and the circadian regulation of metabolism is mediated through reciprocal signaling between the clock and metabolic regulatory networks such as autophagy [44]. Recently, Ryzhikov and colleagues reported that diurnal rhythms spatially and temporarily organize autophagy [55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on our data, there is a need to determine the mechanistic link between diurnal changes and autophagy in the neural retina. There is considerable evidence that diurnal/circadian rhythm is associated with the induction of autophagy [44,53], a key regulator of autophagy; the mechanistic target of rapamycin (mTOR) is regulated by the circadian clock [54] and the circadian regulation of metabolism is mediated through reciprocal signaling between the clock and metabolic regulatory networks such as autophagy [44]. Recently, Ryzhikov and colleagues reported that diurnal rhythms spatially and temporarily organize autophagy [55].…”
Section: Discussionmentioning
confidence: 99%
“…See review [79]. Moreover, the connection between circadian rhythm and mammalian target of rapamycin (mTOR) signaling pathways (crucial for numerous biological processes and metabolism of bone, muscle, and adipose tissue) has been reported recently [80]. Accordingly, the robust circadian rhythm is necessary for the proper functioning of all body processes.…”
Section: Misalignments Of Circadian Rhythmmentioning
confidence: 99%
“…[24][25][26] mTORC1 is capable of coupling environmental inputs, including AA availability, to the circadian clock and its signaling network. Data from a recent review of the non-ruminant literature underscored a reciprocal interplay between circadian clock and mTORC1 signaling, 27 with a key premise being that mTORC1 activity is regulated by the circadian clock. In turn, the rhythmicity of mTORC1 and its downstream signaling components impact autonomous properties as well as core clock proteins both in suprachiasmatic nucleus (SCN) and some peripheral tissues (e.g.…”
Section: Introductionmentioning
confidence: 99%